A novel genetic variant associated with benign paroxysmal positional vertigo within the LOXL1. Issue 10 (22nd August 2020) - Deng, Mingzhu; Liu, Chen; Jiang, Weiqing; Wang, Fei; Zhou, Juan; Wang, Dong; Wang, Yonggang
Abstract: Background: Benign paroxysmal positional vertigo (BPPV) is a common, self‐limited, and favorable prognostic peripheral vestibular disorder. BPPV is transmitted in an autosomal dominant fashion, but most cases occur sporadically. Little research has been reported regarding the mutation spectrum of sporadic BPPV in a large cohort. This study attempted to identify the causative candidate variants associated with BPPV in VDR, LOXL1, and LOXL1 ‐ AS1 . Methods: An amplicon‐targeted next‐generation sequencing (NGS) method for VDR, LOXL1, and LOXL1 ‐ AS1, was completed in 726 BPPV patients and 502 normal controls. A total of 30 variants (20 variants from VDR, nine variants from LOXL1, seven variants from LOXL1 ‐ AS1 ) were identified in these two groups. Results: Three of 30 variants were nonsynonymous mutations, but no significant difference was found between the BPPV group and the control group via association analysis. A single nucleotide variant (SNV), rs1078967, was identified that is located in intron 1 of LOXL1 . The allelic frequency distribution differed significantly between the BPPV group and the control group ( p  = 0.002). Genotypic frequency was also significantly different ( p  = 0.006), as determined by gene‐based analyses. Conclusion: This report is the first to analyze the variant spectrum of BPPV in a large Chinese population. Abstract : Little has been reported about mutation spectrum of sporadically BPPV in a large cohort. A single nucleotide variant (SNv), rs1078967, was identified, which is located in intron 1 of LOXL1. we speculate that the mutation of LOXL1 may lead to the disfunction of the elastogenesis to some extent, which further impairs the adherence of otoconia to the gelatinous matrix, and make it easy to fall off, thus leading to the onset of benign paroxysmal positional vertigo.